A high energy density azobenzene/graphene hybrid: a nano-templated platform for solar thermal storage1. Issue 22 (14th June 2015) - Luo, Wen; Feng, Yiyu; Cao, Chen; Li, Man; Liu, Enzuo; Li, Shipei; Qin, Chengqun; Hu, Wenping; Feng, Wei
<x xml:space="preserve">Abstract</x> A high functionalization density and inter-planar bundling interaction remarkably improve both the storage capacity and lifetime of solar thermal fuels using an azobenzene/graphene nano-template.